Pengaruh Harga, Distribusi, WOM, dan Citra Merek Terhadap Keputusan Pembelian Bistro Bahagia - Frendy Mayhendra Mayhendra; Herry Widagdo (MDP Student Conference, 2026)
This study aims to examine the Influence of Price, Distribution, Word of Mouth and Brand Image on Consumer Purchasing Decisions at the Bistro Bahagia Restaurant in Palembang City, both Partially and Simultaneously. The technique used for data collection is by distributing Questionnaires with a Likert Scale, with a total of 230 Respondents. The type of research used in this study is a Quantitative Approach. The sampling technique uses Non-Probability Sampling using the Accidental Sampling Technique. Data processing of this study uses SPSS 26 Software. The results of this study indicate that Partially, the Price Variable (X1), Distribution (X2), and Brand Image (X4) have a Positive and Significant influence on Consumer Purchasing Decisions. Meanwhile, the Word of Mouth Variable (X3) has a Positive and Insignificant influence on Consumer Purchasing Decisions. This study simultaneously shows that all Independent Variables used, namely Price (X1), Distribution (X2), Word of Mouth (X3), Brand Image (X4) have an influence on Consumer Purchasing Decisions.